High-Dose Tranexamic Acid in Patients Underwent Surgical Repair of Aortic Dissection Might Reduce Postoperative Blood Loss: A Cohort Analysis - Guo, Jingfei; Cao, Liang; Wang, Hongbai; Liu, Guangyu; Zhou, Yong; Yang, Lijing; Jia, Yuan; Yuan, Su (Frontiers in Surgery, 2022)
Introduction： While tranexamic acid（TXA） is widely used in patients with acute type A aortic dissection（ATAAD） who undergo surgical repair to reduce blood loss and transfusion requirement, the optimal dosage of TXA is unknown in these patients. Materials and Methods： This was a retrospective cohort study that compared high-dose(＞50mg/kg) and low-dose TXA(≤50mg/kg) in patients with ATAAD who underwent surgical repair. Propensity score matching (PSM) was performed between the two groups and results were analyzed in matched cases. The primary outcome was postoperative blood loss within 3 days after surgery. The secondary outcomes were total blood loss after surgery and perioperative blood transfusion， and safety outcomes were also assessed. Results： Through medical record screening, 529 patients were identified. After PSM, 196 patients in the high-dose group and 196 patients in the low-dose group were matched and included in the final analysis. Postoperative blood loss in 3 days after surgery was 940ml（710-1010ml）in the low-dose group and 695ml（620-860ml）in the high-dose group. The difference was statistically significant (P＜0.001). Total postoperative blood loss was also statistically less in the high-dose group compared to the low-dose group（1890ml(1410-2100ml）vs. 2040ml (1460-2320ml）, P=0.032）. No difference was found between the two groups in transfusion and safety outcomes. Conclusion： In ATAAD patients who underwent surgical repair, high-dose TXA significantly reduced postoperative blood loss compared to low-dose TXA, while no difference in transfusion or adverse events was found.